Reaching hundreds of millions of the rural poor with sustainable savings and credit services: The role of rural & agricultural banks and their reform in Asia - Hans Dieter Seibel (Universität zu Köln, Arbeitsstelle für Entwicklungsländerforschung (AEF), 2001)
Rural and agricultural banks, among them state-owned agricultural development banks (AgDBs) and cooperative banks, have a wide outreach in Asian countries. Their potential as retailers and wholesalers (through cooperatives, rural banks, NGOs) for providing sustainable savings deposit and credit services to the rural poor is enormous. Some examples: (a) The quantative and qualitative outreach BRI Microbanking Division, with 25.1 million microsavings accounts and 2.6 million current microcredit accounts (at a profit!), surpasses that of some 10,000 formal and semiformal MFIs in Indonesia. (b) BAAC provides near-total coverage in terms of rural saver and agricultural borrower outreach in Thailand. (c) The outreach of NABARD in India through rural banks, financial cooperatives and self-help groups (SHGs) exceeds a hundred million. With regard to outreach to the very poor, NABARD has achieved spectacular success through its program Linking Banks and SHGs, expecting an outreach of a hundred million rural poor by 2008. (d) In Nepal, IFAD and AsDB helped ADB/Nepal to build up a rural financial infrastructure of small farmer groups. With assistance from GTZ, 101 subproject offices have been transformed into autonomous savings and credit cooperatives (SFCLs), with an astonishing ratio of financial self-sufficiency of 117%. The success of the SFCLs in the fertile plains and the marginal hill areas is living proof of the compatability of outreach to the poorest and institutional sustainability even in a most difficult environment. Yet, the large majority of AgDBs in Asia and elsewhere are grossly underperforming and are a major drain on public resources. Therefore, they have been ignored by most donors in recent years. However, experience in Asia shows that there is an enormous potential for reform. There is little chance that the small MFIs donors have been focussing on will even remotely come close to the Summit?s quantitative aims of outreach. Rural and agricultural banks must be included in our joint campaign to combat poverty, and every effort should be made to convince governments to transform rural and agricultural banks into viable and sustainable financial intermediaries with wide outreach to the rural poor. IFAD?s new initiative with CGAP, the World Bank, FAO, GTZ, regional development banks and the RACAs (Afraca, Apraca, Nenaraca) has focused on the potential as well as reform needs of AgDBs and increasingly attracted international attention. By including rural and agricultural banks in the Summit?s agenda, it is expected that synergies will be mobilized with the objective of substantially increasing access of the poor and very poor to sustainable financial services throughout Asia and the Pacific. The Microcredit Summit Campaign may play an important role in generating the necessary political will.
Keywords: 330